Application of System Dynamics in Analyzing the Cultivated Land-Water Resources Carrying Capacity in Bijie Prefecture, China - 何仁伟 刘邵权 李立娜 梁岚 李婷婷 (东华大学学报（英文版）, 2013)
The cultivated land-water resources carrying capacity （CL-WRCC） with the method of system dynamics （SD） were analyzed. Bijie prefecture of Guizhou province served as a case in this study. Bijie prefecture is one of the least-developed areas in China. In Bijie, the physical and chemical characteristics of karst as well as the rapid economic development lead to the scarcities of cultivated land-water resources （CL-WR）. On the basis of analysis on the subsystems of Bijie CL.WRCC system, the fundamental feedback structure of CL-WRCC was presented by causal loop diagram. Considering the three alms （＂ poverty alleviation and development, ecological construction, and population control＂） of Bijie as the major goals, Bijie CL-WRCC SD model was developed. Three scenarios, resource-saving and environment-friendly development-oriented scenario （Scenario 1 ）, fast economic development-oriented scenario （ Scenario 2 ）, and coordinated development-oriented scenario （Scenario 3 ）, were investigated. Simulation results indicate that Scenario 3 which takes social economic development, environment protection, and cultivated land- water resources utilization into account, is the best alternative scenario. It can promote the coordination development of society, economy, cultivated land, water resources, and environment. In this study, the technological support and the decision-making for the rational use of CL-WR are provided not only in Bijie, but also in other similar regions of China.